2021
DOI: 10.1007/s40618-021-01513-8
|View full text |Cite
|
Sign up to set email alerts
|

High urinary excretion rate of glucose attenuates serum uric acid level in type 2 diabetes with normal renal function

Abstract: Aims/Introduction The relationship between urinary excretion rate of glucose (UEGL) and uric acid (UA) metabolism in adults with type 2 diabetes (T2D) remains unclear to date. This study aimed to investigate the relationships of UEGL with serum UA (SUA), urinary excretion rate of uric acid (UEUA), and renal clearance of uric acid (CLUA) in adults with T2D. We hypothesised that high UEGL increases UA excretion, which in turn leads to lower SUA. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…In contrast to the HUA, the AH is insidious. Continuous research has shown that continuously increasing UA levels are also closely related to many diseases, such as diabetes [ 2 ], hypertension [ 3 ], stroke [ 4 ], and myocardial infarction [ 5 ]. It also suggests the great harm of the AH.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the HUA, the AH is insidious. Continuous research has shown that continuously increasing UA levels are also closely related to many diseases, such as diabetes [ 2 ], hypertension [ 3 ], stroke [ 4 ], and myocardial infarction [ 5 ]. It also suggests the great harm of the AH.…”
Section: Introductionmentioning
confidence: 99%
“…The role of hyperuricemia as a potential cardiovascular risk factor should not be overlooked, as UA can promote the development of hypertension, atherosclerosis, fibrillation, and heart failure [ 76 ]: however, a recent meta-analysis study has highlighted that hyperuricemia, while potentially independently contributing to endothelial dysfunction, is more likely to be a reliable marker of systemic dysmetabolic disorders which might negatively affect erectile function [ 77 ]. Obesity, diabetes mellitus (and “diabesity”), chronic kidney disease, hypertension, metabolic syndrome, hypovitaminosis D, use of diuretics, and peripheral vascular disease are known risk factors and comorbidities for gout [ 78 82 ], which can potentially act on an already established state of asymptomatic hyperuricemia, promoting progression to clinical disease. These comorbidities, however, are also well known to sexual medicine experts: obesity, insulin resistance, hypertension, and the use of diuretics are known risk factors for the development of sexual dysfunctions in both men [ 13 , 15 , 17 , 83 85 ] and women [ 83 , 84 , 86 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, which involved healthy people without diabetes ( n = 102), prediabetes ( n = 98), and diabetes ( n = 110), an inverse association was found between the SUA and fasting glucose levels and the prevalence of diabetes ( 37 ). These observations might be explained by higher renal clearance of uric acid in adult diabetic patients ( 38 ). The following reasons could potentially explain the differences in the above studies: (1) the participants involved in previous studies had different characteristics.…”
Section: Discussionmentioning
confidence: 99%